History of Islamic Thought: trade in the Era of Rosulullah became a guideline for online buying and selling (Olshop) - Kholidatul Mila; Khusnudin (al-Afkar, Journal For Islamic Studies, 2025)
This research focuses on trading practices during the time of Rosulullah and online trading practices, this research will cover the analysis of the trading system. This research uses the study literature method to examine trade practices in the era of Rosulullah and the Contemporary era, the focus of this research lies on trade practices, regulations, strategies and trade applications in the era of Rosulullah and the Contemporary era. Data will be collected through relevant literature, such as historical books about Rosulullah, the works of Islamic historians and economists, as well as primary sources such as historical documents and official documents about Rosulullah. The result of this study is that trade practices during the era of Rosulullah had an advantage in terms of emphasizing the importance of honesty and justice in transactions. He was known as Al-Amin (the trustworthy one), and this created trust among traders.